2008
DOI: 10.1016/j.eplepsyres.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

“Resting” CBF in the epileptic baboon: Correlation with ketamine dose and interictal epileptic discharges

Abstract: Background Photosensitive epileptic (SZ) baboons demonstrate different cerebral blood flow (CBF) activation patterns from asymptomatic controls (CTL) during intermittent light stimulation (ILS). This study compares “resting” CBF between PS and CTL animals, and CBF correlations with ketamine dose and interictal epileptic discharges (IEDs) between PS and CTL animals. Methods Continuous intravenous ketamine was administered to eight PS and eight CTL baboons (matched for gender and weight), and maintained at sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Furthermore, ketamine was used to lightly sedate the baboons. As mentioned above, ketamine can alter resting CBF in a dose-dependent fashion (Szabó et al 2008), particularly in epileptic baboons. It can also induce IEDs or seizures at low doses (Szabó et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ketamine was used to lightly sedate the baboons. As mentioned above, ketamine can alter resting CBF in a dose-dependent fashion (Szabó et al 2008), particularly in epileptic baboons. It can also induce IEDs or seizures at low doses (Szabó et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These regions were not included in our model because they did not demonstrate significant CBF changes during the PPR in earlier conditional contrast and covariance studies (Szabó et al 2007; Szabó et al 2011). The thalamus is another structure extensively connected with the frontoparietal cortices, which is typically activated in the setting of prolonged generalized spike-and-wave discharges or absence seizures in humans (Bai et al 2010; Benuzzi et al 2012), and in the setting of sustained repetitive IEDs in the epileptic baboon (Fischer-Williams et al 1968; Szabó et al 2008; Silva-Barrat et al 1986). However, as most of the PPRs were brief and PCRs were restricted to brief myoclonic seizures in the PS baboons, it not surprising that the thalamus was not involved or significantly activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of i.v. ketamine anesthesia may influence the magnitude and distribution of cortical and subcortical CBF changes (Szabó et al 2008). Långsjö et al, 2003 found that ketamine induces a global, concentration-dependent increase in CBF with the largest increases in the anterior cingulate, thalamus, putamen, and frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The baboon’s large brain size makes them more suitable for magnetic resonance imaging (MRI) and positron emission tomography (PET) studies, increasing its potential as a possible model for functional imaging studies of ischemia and neurological disorders—e.g. stroke (Fukuda & del Zoppo 2003) and epilepsy (Szabó et al, 2008; Szabó et al, 2011). The baboon’s larger brain size also permits the use of standard (human) TMS coils since the induced electric fields (E-fields) will be focally distributed in a larger brain volume than in smaller NHPs—i.e.…”
Section: Introductionmentioning
confidence: 99%